Evaluation of the Accuracy and Performance of Two Commercial Pregnancy‐Associated Glycoprotein Tests for Early Pregnancy Detection in Cows - Safak, Tarik; Tümer, Kenan Çağrı; Alp, Yağmur İpek; Özen, Taha Yasin; Yilmaz‐Koc, Oznur (Wiley, 2025)
ABSTRACTThe aim of this study was to determine and compare the diagnostic accuracies of two commercial pregnancy‐associated glycoprotein tests, Alertys OnFarm Pregnancy Test (AOPT) and Alertys Milk Pregnancy Test (AMPT), for early pregnancy diagnosis in dairy cattle. Holstein cows (n = 124) were used in the study. Whole blood samples were collected from the jugular vein 28 days after fixed‐time artificial insemination (FTAI). In addition, teats of these cows were swabbed and milk samples were collected into sterile Falcon tubes. AOPT was performed on the farm within 2 h after whole blood collection. Milk samples for AMPT analysis were taken to the laboratory and analysed within 2 h. Transrectal ultrasonography was performed on the 32nd day after FTAI as a reference test. Comparative evaluation was made according to the AOPT and AMPT results, 28 days after FTAI. The sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV) for the AOPT were 92.4%, 80.0%, 87.9%, 89.0% and 85.7% and for AMPT were 97.5%, 82.2%, 91.9%, 90.6% and 94.9% respectively. Cohen's kappa statistic showed a 91.9% agreement (kappa = 0.820, p < 0.001) between the reference test and AMPT, and an 87.9% agreement (kappa = 0.735, p < 0.001) between the reference test and AOPT. AOPT and AMPT offers a reliable, non‐invasive (in milk) and practical approach to pregnancy diagnosis in cows. These methods enable early pregnancy detection and can be easily integrated into farm routines, enhancing reproductive management and overall herd productivity.
Keywords: Pregnancy Tests; Veterinary medicine; cow; Pregnancy Proteins; pregnancy‐associated glycoproteins; pregnancy‐associated glycoproteins.; Sensitivity and Specificity; Milk Pregnancy Test; Milk; Pregnancy; Predictive Value of Tests; SF600-1100; Animals; Original Article; Female; Cattle; OnFarm Pregnancy Test